Consumer Position Theory in Relation to Criminal Law Policies on Glue Abuse - Widarsono Widarsono; Sodikin Sodikin (Jurnal Indonesia Sosial Sains, 2026)
This study discusses the legal vacuum surrounding the abuse of addictive substances, particularly in cases of illegal glue use among young people, which has become increasingly concerning for society. Across Indonesia, there have been several cases of death resulting from the misuse of addictive substances contained in glue. The main issue examined concerns criminal law policy as part of state legal politics and the theory of consumer position in relation to the abuse of glue containing addictive substances. The research method employed is normative descriptive, utilizing both legislative and conceptual approaches. The results of the study explain that, according to the Consumer Position Theory, a contract is not a prerequisite for imposing an obligation on business actors to protect consumers. This obligation exists regardless of whether a contractual relationship is established. Therefore, with or without a contract between business actors and consumers, the responsibility of business actors to protect their consumers remains. Business actors must not prioritize profit alone. Moreover, even if a business actor has informed consumers about the potential hazards of a product to life or health, this does not automatically exempt the business actor from criminal liability. Each case must instead be examined individually based on its specific circumstances.